2021
DOI: 10.1016/j.celrep.2021.109025
|View full text |Cite
|
Sign up to set email alerts
|

SLC22A14 is a mitochondrial riboflavin transporter required for sperm oxidative phosphorylation and male fertility

Abstract: Summary Ablation of Slc22a14 causes male infertility in mice, but the underlying mechanisms remain unknown. Here, we show that SLC22A14 is a riboflavin transporter localized at the inner mitochondrial membrane of the spermatozoa mid-piece and show by genetic, biochemical, multi-omic, and nutritional evidence that riboflavin transport deficiency suppresses the oxidative phosphorylation and reprograms spermatozoa energy metabolism by disrupting flavoenzyme functions. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…show that an altered riboflavin level causes spermatozoa morphological and bioenergetic defects in mice (Kuang et al, 2021). Riboflavin has recently been used to assist cryopreservation of platelets (Jimenez-Marco et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…show that an altered riboflavin level causes spermatozoa morphological and bioenergetic defects in mice (Kuang et al, 2021). Riboflavin has recently been used to assist cryopreservation of platelets (Jimenez-Marco et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Addition of antioxidants to freezing extenders could help spermatozoa against oxidative stress and improve the viability of sperm after freeze‐thawing (Naijian et al., 2013). Some researchers have demonstrated the antioxidant function of riboflavin (Tang et al., 2014), and show that an altered riboflavin level causes spermatozoa morphological and bioenergetic defects in mice (Kuang et al., 2021). Riboflavin has recently been used to assist cryopreservation of platelets (Jimenez‐Marco et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in this study, we found that HT enhanced the plasma levels of flavonoids and riboflavin. It has been shown that flavonoids and flavanone metabolites, such as naringenin 7-O-glucuronide and 3,4-dihydroxyphenylglycol, had powerful antioxidant ability, thus they may contribute to improved sperm quality and function (35)(36)(37)(38). 6-Hydroxymelatonin (increased by HT) is one of the metabolites of melatonin and has been shown to have strong antioxidant activity (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, follow‐up studies have shown that the orphan transporter SLC16A13, which is located next to SLC16A11 on chromosome 17p13.1, is a lactate transporter and also plays a role in type 2 diabetes 38 Using knockout mice, riboflavin was identified as the major substrate of SLC22A14, which was an orphan at the time 39 . Detailed studies showed that riboflavin plays an important role in the testis and reduced uptake of riboflavin in male SLC22A14 knockout mice resulted in infertility. Using in silico analysis, the gene SLCO1B7 previously considered as pseudogene, was predicted to have 11 transmembrane domains.…”
Section: Basic Transporter Researchmentioning
confidence: 99%